(untitled) - David C. Lay (Reading, Mass, 1996)
Linear algebra is relatively easy for students during the early stages of the course, when the material is presented in a familiar, concrete setting. But when abstract concepts are introduced, students often hit a "brick wall." Instructors seem to agree that certain concepts (such as linear independence, spanning, subspace, vector space, and linear transformations), are not easily understood, and require time to assimilate
Keywords: Algebras, Linear,Đại số tuyến tính; Textbooks,Giáo trình